Perhitungan Kebutuhan Kapasitas Tampung bagi Rencana Pengembangan Areal Layanan Irigasi dari Bendung Perjaya – Sumatera Selatan dengan Metode Numerik dan “Sequent Peak” - Agung Bagiawan (Balai Teknik Irigasi, 2013)
The development of an irrigated area is strongly influenced by water availability, water demand and availability of infrastructure. Water balance is the key to whether the water system in the irrigation area development plan can be realized according to currently existing condition because of an availability of water surplus, without needing improvement of existing dam efficiency and effectiveness. If there is a deficit of water, it still may require an amount of water through the construction of a reservoir upstream. In support of the development plan, a simulation between the extent of proposed irrigated area and water available is required, so that weir capacity for any alternative to the irrigation area development can be identified to meet the needs of development. Some simple methods and calculations can be used to simulate the required capacity of a weir upstream.